Development of Interactive Learning Media on Material Writing Short Story Texts Based on Experience - Mastari Ramadhani; M. Oky Fardian Gafari; Marice Marice (BIRCU, 2019)
The development of interactive media on learning to write experience-based short stories is designed according to the needs and characteristics of students who are expected to be able to overcome all the problems in learning activities to write short stories and make students more active, independent and able to think critically. This research was carried out at Amanah Islamic Modern School Middle School in Medan. The data in this study are the results of observations, interviews, results of questionnaires validation of material and design of learning media, the results of questionnaires teacher perceptions of learning media developed, and student learning outcomes totaling 32 people. Data from observations in the form of learning values writing short stories totaling 32 students so far and the results of interviews in the form of opinions of two Indonesian language teachers related to learning to write short stories obtained from students and teachers of Indonesian. Learning outcomes in short story text writing material based on the experience of students of class IX-1 Amanah Middle School Islamic Modren School Medan after using interactive learning media are in the category of